Changing Diets: Eating habits of immigrants from the other former Yugoslavian republics in Slovenia - Zevnik, Luka; Stankovič, Peter (Two Homelands, 2010)
A significant minority of immigrants from the other former Yugoslavian republics lives in Slovenia. In research based on qualitative methodology, authors look for possible changes that happened to the immigrants' culinary practices in Slovenia, whereby they are primarily interested in the interpretative schemes that the immigrants employ when reflecting upon these changes. The results show a large amount of pragmatism in relation to the culinary choices, fatalism with respect to the limitations they are encountering in their newly adopted environment, an almost complete absence of nationalist discourses, and an impressive amount of tolerance towards any kind of possible culinary differences.